Australian women's complex engagement with the yummy mummy discourse and the bodily ideals of good motherhood. (May 2017) - Malatzky, Christina Amelia Rosa
Abstract: The celebrity "yummy mummy" is a popular and dominant contemporary representation of motherhood. Feminist analyses of the yummy mummy have predominately focused on textual readings of the Western cultural ideal of the maternal. This paper contributes to this body of scholarship by focusing on empirical data gathered from 29 women living in regional Western Australia. Representations of the yummy mummy regulate how women experience their bodies and their identities as mothers, and how they perceive other women. Analysing these representations provides a platform for talking about maternal bodies and the current societal pressures upon them, with the mothering ideal associated with the yummy mummy being in deep conflict with other dominant ideas about what constitutes good mothering. I argue that while women do not have many alternative discourses to draw on, they can engage in resistance work against the powerful ideal of the yummy mummy, often at the same time as desiring it. Highlights: There are few alternative discourses available to women to critique the yummy mummy. The yummy mummy ideal influences feelings about and relations to the postnatal body. The "self-conscious" internalising of the ideal holds possibilities for resistance. Reflexivity can produce other discourses to (re)construct maternal subjectivities.